İleri osmoz prosesi kullanılarak peynir altı atıksuyunda (PAS) hacim azaltımı üzerine çekme çözeltisi ve ozmotik basınçın etkisi - Kuvvet, Ferihan (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2012)
Bu çalışmada, peyniraltı suyu hacminin azaltılması üzerine çekme çözeltisi türü ve buna bağlı olarak da osmotik basıncın etkisi araştırılmıştır. 5 farklı çekme çözeltisi türü (NaCl, KCl, CaCl2 ve MgCl2) için FO prosesinde performans ve membran kirlenmesi incelenmiştir. Performans parametreleri olarak su akısı, tuz akısı, net ve etkili osmotik basınçlar, PAS'ın konsantre olma oranı ve toplam katı içeriği değişimleri izlenmiştir. Membran kirlenmesi ise taramalı electron mikroskobu, atomik kuvvet mikroskobu, Fourier kızılötesi dönüşüm spektroskopisi ve temas açısı yüzey karakterizasyonu ölçümleriyle analiz edilmiştir. Ayrıca model çalışmalarıyla da, deneysel tuz ve su akıları modellenerek tuz geçirgenlik katsayısı ve çözünmüş madde dirençliliği parametreleri tespit edilmiş, kirlenme ? performans ilişkileri ortaya konmuştur. Proseste en fazla susuzlaştırma, % 23'lük performans ile NaCl tuzu kullanılarak elde edilmiştir. Toplam katı madde, NaCl tuzu ile % 6.79'dan % 8.75 değerine çıkarılmıştır. Proseste, tek değerlikli sodyum ve potasyum klorür tuzlarıyla, iki değerlikli tuzlara nazaran daha iyi su geçiş performansı elde edilmiştir. FO prosesinde etkili osmotik basınç değerlerinin, çalışılan tuz türünün tamamı için net osmotik basınç farkı değerlerinden oldukça düşük seviyelerde kaldığı belirlenmiştir. Buna göre, FO prosesinde etkin işletme sağlanabilmesi için bu prosese uygun çok özel tasarımlar gerektiren membranların geliştirilmesine ihtiyaç bulunduğu anlaşılmaktadır. Organik karbon, azot ve fosfor bileşenleri itibariyle PAS'tan çekme çözeltisine farklı seviyelerde kirlilik geçişleri olduğu gözlenmiştir. Çekme çözeltilerine N ve P bileşenlerinin düşük seviyelerde geçişlerine rağmen, düşük moleküler ağırlıklı proteinler ağırlıklı çözünmüş organik moleküller sebebiyle dikkate değer organik kirlilik geçişleri belirlenmiştir. Temas açısı ve AFM sonuçlarına göre, KNO3 tuzunun membranın aktif tabakasında hemen hemen herhangi bir kirlenmeye sebep olmadığı tespit edilmiştir. Aktif tabaka üzerinde en çok yüzey kirlenmesi MgCl2 tuzunun çözünmüş iyonlarına dayalı olarak oluşmuş, iki değerlikli tuzlar aktif tabaka üzerinde rölatif olarak dahaçok inorganik kirlenmeye neden olmuştur. Oysa en iyi su geçişi sağlayan NaCl tuzu iyonlarının dış kirlenme üzerine etkisi, destek tabakası üzerinde daha baskın gerçekleşmiştir. Buna karşın, FTIR analizlerine göre, NaCl ile her iki tabaka üzerinde en yüksek organik kirlenmeler gözlenmiştir. Modelleme neticesinde, bu tuz ile beslemeye en yüksek tuz geçiş akısına karşılık, KNO3 tuzu hariç bu tuzun membran içerisinde rölatif olarak daha düşük kirlenme oluşturduğu belirlenmiştir. Ayrıca, çekmedeki tuz katyonunun artan iyon yükü, membranın tuz geçiş akısı ve tuz geçirgenliğini çok arttırmamasına rağmen, membran içerisindeki kirlenmede önemli artışlara sebep olduğu tespit edilmiştir.In this study, it was investigated how the types of extraction solution and osmotic pressure in parallel with the extraction solution affect that volume of the water under the cheese was decreased. The performance parameters which are water flux, salt flux, net and effective osmotic pressures, the concentration ratio of PAS and total solid contents were analyzed during the study. The membrane fouling was characterized by using Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), Fourier Transfromation Infrared Spectroscopy (FTIR) and contact angle surface chracterization technique. Furthermore, the parameters of permeability coefficient and solute resistance were determined by modelling of the experimental water and salt fluxes and the relation between pollution and performance was exhibited. The best water removing performance (23 %) was obtained in the presence of NaCl. Total solid contents was increased from 6.79 % to 8.75 % due to the NaCl. When we compared NaCl and KCl with two valances salts, better water transfer performance was observed in the presence of alkali salts. In forward osmozis process, it was determined that the effective osmotic pressure values are lower than the net osmotic pressure differences for all types of salts. Therefore, it is understood that the specific designs should be developed for this process in order to provide the efficient operation. The other important observation is that pollution transitions from PAS to extraction solution are in different levels because of the organic carbon, nitrogen and phosphorus components. Although the transition of N2 and P in to the extraction solution is at low level, the organic pollution transition is at considerable level due to proteins with low molecular weight in solution. Contact angle and AFM results indicated that KNO3 does not lead any fouling on the active layer of the membrane. The most surface fouling on the active layer occured depending on the dissolved ions of MgCl2 and it was concluded that salts with two valances cause more anorganic fouling, relatively. On the other hand, the fouling effect of NaCl ions which are provided the best water transition wasformed as more dominant on the support layer. According to FTIR analysis results, it was observed the highest fouling for each layers in the presence of NaCl. The results of modellingindicated even if NaCl feeding rate is the highest, except for KNO3, this salt leads to the lower fouling in the membrane relatively. Lastly, it is determined that although the increase of ion charge of salt cation in the extraction solution does not increase the salt permeability and salt flux of membrane highly, it plays an important role in the membrane fouling.

In this study, it was investigated how the types of extraction solution and osmotic pressure in parallel with the extraction solution affect that volume of the water under the cheese was decreased. The performance parameters which are water flux, salt flux, net and effective osmotic pressures, the concentration ratio of PAS and total solid contents were analyzed during the study. The membrane fouling was characterized by using Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), Fourier Transfromation Infrared Spectroscopy (FTIR) and contact angle surface chracterization technique. Furthermore, the parameters of permeability coefficient and solute resistance were determined by modelling of the experimental water and salt fluxes and the relation between pollution and performance was exhibited. The best water removing performance (23 %) was obtained in the presence of NaCl. Total solid contents was increased from 6.79 % to 8.75 % due to the NaCl. When we compared NaCl and KCl with two valances salts, better water transfer performance was observed in the presence of alkali salts. In forward osmozis process, it was determined that the effective osmotic pressure values are lower than the net osmotic pressure differences for all types of salts. Therefore, it is understood that the specific designs should be developed for this process in order to provide the efficient operation. The other important observation is that pollution transitions from PAS to extraction solution are in different levels because of the organic carbon, nitrogen and phosphorus components. Although the transition of N2 and P in to the extraction solution is at low level, the organic pollution transition is at considerable level due to proteins with low molecular weight in solution. Contact angle and AFM results indicated that KNO3 does not lead any fouling on the active layer of the membrane. The most surface fouling on the active layer occured depending on the dissolved ions of MgCl2 and it was concluded that salts with two valances cause more anorganic fouling, relatively. On the other hand, the fouling effect of NaCl ions which are provided the best water transition wasformed as more dominant on the support layer. According to FTIR analysis results, it was observed the highest fouling for each layers in the presence of NaCl. The results of modellingindicated even if NaCl feeding rate is the highest, except for KNO3, this salt leads to the lower fouling in the membrane relatively. Lastly, it is determined that although the increase of ion charge of salt cation in the extraction solution does not increase the salt permeability and salt flux of membrane highly, it plays an important role in the membrane fouling.
The effects of extraction solution and osmotic pressure on the volume decrease of waste water under cheese by using the forward osmozis process
Keywords: Çevre Mühendisliği; Environmental Engineering